Chiesa e pedofilia, il caso italiano Presentazione del libro di Federico Tulli Roma, 30 maggio 2014 - Vari, Autori (Il sogno della farfalla, 2015)
We are publishing the speeches delivered at the book launch of Federico Tulli’s book Chiesa e pedofilia, il caso italiano (L’Asino d’oro editions, Rome 2014), which exposes the high incidence of sexual abuse carried out by Catholic priests on children in Italy too and how church officials are highly responsible for covering up these crimes. Philosophical historian, Fulvio Iannaco, and psychiatrists psychotherapists Domenico Fargnoli and Andrea Masini and the author himself explore the phenomenon from a historical, philosophical and psychopathological point of view, locating its deep seated roots in Christian ideology and in a plurimillennial culture that has annulled the child’s human identity.